Recurrent FOSL1 rearrangements in desmoplastic fibroblastoma. Issue 2 (3rd January 2023) - De Noon, Solange; Piggott, Robert; Trotman, Jamie; Tadross, John A; Fittall, Matthew; Hughes, Debbie; Ye, Hongtao; Munasinghe, Emani; Murray, Matthew; Tirabosco, Roberto; Amary, Fernanda; Coleman, Nicholas; et al.
Abstract: The FOS gene family has been implicated in tumourigenesis across several tumour types, particularly mesenchymal tumours. The rare fibrous tumour desmoplastic fibroblastoma is characterised by overexpression of FOSL1. However, previous studies using cytogenetic and molecular techniques did not identify an underlying somatic change involving the FOSL1 gene to explain this finding. Prompted by an unusual index case, we report the discovery of a novel FOSL1 rearrangement in desmoplastic fibroblastoma using whole‐genome and targeted RNA sequencing. We investigated 15 desmoplastic fibroblastomas and 15 fibromas of tendon sheath using immunohistochemistry, in situ hybridisation and targeted RNA sequencing. Rearrangements in FOSL1 and FOS were identified in 10/15 and 2/15 desmoplastic fibroblastomas respectively, which mirrors the pattern of FOS rearrangements observed in benign bone and vascular tumours. Fibroma of tendon sheath, which shares histological features with desmoplastic fibroblastoma, harboured USP6 rearrangements in 9/15 cases and did not demonstrate rearrangements in any of the four FOS genes. The overall concordance between FOSL1 immunohistochemistry and RNA sequencing results was 90%. These findings illustrate that FOSL1 and FOS rearrangements are a recurrent event in desmoplastic fibroblastoma, establishing this finding as a useful diagnostic adjunct and expanding the spectrum of tumours driven by FOS gene family alterations. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.